A pragmatic approach to embedding patient blood management in a tertiary hospital. Issue 4 (8th August 2013) - Leahy, Michael F.; Roberts, Heather; Mukhtar, S. Aqif; Farmer, Shannon; Tovey, Julie; Jewlachow, Val; Dixon, Tracy; Lau, Peter; Ward, Michael; Vodanovich, Matthew; Trentino, Kevin; Kruger, Paul C.; et al.
<x xml:space="preserve">Abstract</x> Background We describe the implementation and impact of a patient blood management program (PBMP) in an Australian teaching hospital. Study Design and Methods A PBMP was introduced at a single tertiary care hospital in 2009 as a pilot for the Western Australian Health Department statewide PBMP. The first 3 years of interventions aimed to make effective use of preoperative clinics, manage perioperative anemia, improve perioperative hemostasis, reduce blood sample volumes, and implement restrictive transfusion triggers and a single‐unit transfusion policy. Results Between 2008 and 2011, admissions to Fremantle Hospital and Health Services increased by 22%. Using 2008 as a reference year, the mean number of red blood cell (RBC) units per admission declined 26% by 2011. Use of fresh‐frozen plasma and platelets showed 38 and 16% declines, respectively. Cryoprecipitate increased 7% over the 4‐year period. For elective admissions between 2008 and 2011, the leading decline in RBC transfusion rate was seen in cardiothoracic surgery (27.5% to 12.8%). The proportion of single RBC unit use increased from 13% to 28% (p < 0.001), and the proportion of double units decreased from 48% to 37% (p < 0.001). Conclusion This is the first tertiary hospital in Australia to establish a multidisciplinary multimodal PBMP. Interventions across disciplines resulted in decreased use of RBC units especially in orthopedic and cardiothoracic surgery. Continuing education and feedback to specialties will maintain the program, improve patient outcomes, and decrease the transfusion rate.